(untitled) (Journal of Education and Development, 2024)
In the context of the era of New Quality Productive Forces, technological innovation has become the core force to promote the development of social productivity, which is closely linked with vocational education, and together create a strong demand for high-quality technical and skilled personnel. In order to meet this demand, vocational education must synchronize with the development of the New Quality Productive Forces and form a mechanism of mutual promotion. The key to promoting the high-quality development of vocational education lies in taking technological innovation as the guide, and comprehensively improving the quality of education through measures such as innovating the education model, deepening the integration of industry and education, and enhancing the adaptability of specialties. To this end, vocational education should actively build bridges for the integration of industry and education, enhance the flexibility and adaptability of the education system, innovate the mechanism of talent cultivation, and establish a comprehensive quality assurance system. Together, these efforts will promote vocational education to enter a new stage of high-quality development and provide a solid talent guarantee for the sustainable development of the social economy.